Primo es homo, secundo christianus, deinde vocatus ad hoc vel illud: Some Remarks on the "Imago Dei" as Key to the Unfolding of Being Human and Cultural - Dupré, Wilhelm (Studies in spirituality, 2018)
By approaching the human being as image of God Cusanus resumed, like Augustine before him, a theme of the biblical tradition. However, by interpreting this being in terms of a living image he opened a new road which enabled him to bring the whole spectrum of humanity into perspective. Since novelty and creativity are essential features of the living image, it is both the past and the future of being human and cultural, no less now than at the time of Cusanus, which turn out to be the subject of inquiries. The paper is an attempt to outline some of the ramifications which come along with the idea of the living image.